Non-pharmacological therapies in the management of cervicogenic headache: a literature review - Leite , Milena Maciel; Lustosa , Laissa da Veiga; Fernandes, João Victor de Aguiar; Gonçalves , Yasmim Silveira; Santos, Maria Eduarda Freire dos; Horta, Wagner Gonçalves (Headache Medicine, 2024)
INTRODUCTION Cervicogenic headache (CGH) is a secondary headache with a prevalence of 17.8% among headaches. It impacts quality of life, causing disability in social activities. CGH manifests as unilateral headache accompanied by nausea, neck pain, phonophobia, and photophobia. Differential diagnosis includes migraine, cervical spondylosis, and tension-type headache. Treatment combines pharmacological approaches with non-drug therapies, although there is controversy in the literature regarding which non-pharmacological options are most effective.OBJECTIVES Analyze the most effective non-pharmacological therapies for improving the quality of life of patients with cervicogenic headache.METHODOLOGY This is a literature review using the Medline database via PubMed, with the descriptors "Cervicogenic headache" and "Quality of life," combined with the Boolean operator "AND." A search filter was applied for "title/abstract," and articles published in the last 5 years were included. The inclusion criteria were articles with meta-analysis and literature reviews, resulting in 9 articles in English. The exclusion criteria were articles which were not available for reading and those dealing with neck pain, leaving 7 articles for analysis.RESULTS Physical therapy is the first-line treatment for CGH. Sustained Natural Apophyseal Glides (SNAG) mobilizations lead to favorable outcomes and improve the cognitive-affective aspect of pain. Spinal manipulative therapy reduces the intensity and frequency of pain, though its effects are small and short-term. Cervical decompression surgery has shown positive results in patients with CGH associated with cervical spondylotic myelopathy, indicating a neuropathic pain mechanism for CGH. Dry-needling reduces the frequency of CGH in the short term. However, it is recommended not to apply this therapy in isolation, but to combine it with pharmacological treatment to obtain better results.CONCLUSION Therapies with a pharmacological and non-pharmacological approach, such as physiotherapy, dry needling, and even surgery, constitute the current relief practices for cervicogenic headache. Therefore, the heterogeneity of techniques does not allow the most effective one to be chosen, but it does allow them to be combined for the individual management of each patient in order to improve quality of life, aiming to reduce the intensity and frequency of episodes.